2019
DOI: 10.1177/2309499019836012
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary nail versus external fixator for ankle arthrodesis in Charcot neuroarthropathy: A meta-analysis of comparative studies

Abstract: Purpose: Ankle Charcot neuroarthropathy presents a great challenge for treatment. While conservative treatments yield poor results, arthrodesis is considered the treatment of choice for unstable Charcot ankles. There are two methods used for ankle fusion: retrograde intramedullary nail (IMN) and external fixator (EF). Literature reports inconclusive results on which method is better for arthrodesis. Methods: The aim of this meta-analysis is to look for significant difference between the two techniques in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…Yammine and Assi 18 showed no definitive superiority in their review of four comparable studies with a total of 117 participants. In the case of plantar ulcers and infected Charcot feet, external fixation offers the possibility of surgical eradication of infection together with correction of foot deformities 18–20 . In our study, we had many infected ulcers and osteomyelitis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Yammine and Assi 18 showed no definitive superiority in their review of four comparable studies with a total of 117 participants. In the case of plantar ulcers and infected Charcot feet, external fixation offers the possibility of surgical eradication of infection together with correction of foot deformities 18–20 . In our study, we had many infected ulcers and osteomyelitis.…”
Section: Discussionmentioning
confidence: 97%
“…Both methods have shown advantages and disadvantages in previous studies and so far, no superiority has been found 17 . Yammine and Assi 18 showed no definitive superiority in their review of four comparable studies with a total of 117 participants. In the case of plantar ulcers and infected Charcot feet, external fixation offers the possibility of surgical eradication of infection together with correction of foot deformities 18–20 .…”
Section: Discussionmentioning
confidence: 97%
“…It is still controversial whether internal or external fixation as the most suitable method. The argument is that internal fixation reduces the risk of infection, which is a major problem in CN foot caused by the diabetic condition [ 9 , 10 ]. For the second case the team choose a single distal tibia locking plate for the arthrodesis of the tibiocalcaneal joint planted in the anterior part of the foot.…”
Section: Discussionmentioning
confidence: 99%
“…Since no cast is usually required following ring fixator, swelling and ulcer recurrence could be monitored. On the other hand, advocates of retrograde nails cite the high incidence of pin tract infections, risk of tibia fracture, and the need for a second surgery for EF removal as reasons to choose a nail over EF [1,2,3]. The aim of the present study was to compare the results of EF and retrograde IMN in ankle arthrodesis for patients with Charcot neuroarthropathy of the ankle joint.…”
Section: Introductionmentioning
confidence: 96%
“…Charcot neuropathic osteoarthropathy or neuroarthropathy of the foot and ankle is due to sensory and motor neuropathies which lead to a chronic and progressive destruction of the foot architecture involving bones, joints, and soft tissues. Secondary fractures and dislocations predispose to deformity and ulceration with a great decrease of the gait-related quality of life and an increasing potential for major amputation [1]. Fusion is usually the surgical treatment which is indicated in severe, progressive, unstable deformity of the hindfoot.…”
Section: Introductionmentioning
confidence: 99%